2004
DOI: 10.1097/01.tp.0000112381.80964.85
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma as a dermal scaffold for the generation of a completely autologous bioengineered skin

Abstract: Our data demonstrate that this new dermal equivalent allows for (1) generation of large bioengineered skin surfaces, (2) restoration of both the epidermal and dermal skin compartments, and (3) functional epidermal stem-cell preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
192
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(210 citation statements)
references
References 26 publications
1
192
0
5
Order By: Relevance
“…13 In our setting, correction was achieved by using a conventional retroviral vector and a cultured skin equivalent to accomplish permanent epidermal regeneration in patients. 4 Our results evidenced that the size of the retroviral genome does not hamper its efficient packaging into the viral capsid and generation of infectious viral particles. All three studies on transfer of collagen VII cDNA referred to above showed appropriate protein delivery at basement membrane of the dermal-epidermal junction and stable correction of the RDEB hallmarks of the reverted human skin regenerated onto grafted immunodeficient mice.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 58%
See 1 more Smart Citation
“…13 In our setting, correction was achieved by using a conventional retroviral vector and a cultured skin equivalent to accomplish permanent epidermal regeneration in patients. 4 Our results evidenced that the size of the retroviral genome does not hamper its efficient packaging into the viral capsid and generation of infectious viral particles. All three studies on transfer of collagen VII cDNA referred to above showed appropriate protein delivery at basement membrane of the dermal-epidermal junction and stable correction of the RDEB hallmarks of the reverted human skin regenerated onto grafted immunodeficient mice.…”
Section: Candidate Diseases For Permanent Keratinocyte Gene Transfermentioning
confidence: 58%
“…Furthermore, permanent epithelial regeneration in burn patients treated with cultured keratinocyte autografts (which are not genetically modified) evidence the persistence of functional stem cells. [2][3][4] Experimental evidence also indicated that genetic manipulation does not alter epidermal stemness. 5,6 In the past, however, the long-term persistence of the transgene expression in human keratinocytes in vivo has been difficult to obtain, and generated a long-lasting controversy.…”
Section: Permanent Correction Of a Genetic Disordermentioning
confidence: 99%
“…The remaining cells were frozen as previously described. 8 From a primary culture, 3 ASEs of 75 cm 2 each were obtained. To avoid keratinocyte differentiation, the submerged method was used.…”
Section: Engineering Asementioning
confidence: 99%
“…Subsequently, the biopsies were processed as previously described. 8,9 Briefly, the samples were divided into small fragments and subjected to 4 washes with phosphate buffered saline 5 mL containing trypsin and ethylenediaminetetraacetic acid (Gibco, Paisley, Invitrogen, UK) at concentrations of 0.05% and 0.02%, respectively.…”
Section: Engineering Asementioning
confidence: 99%
See 1 more Smart Citation